(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
In the article, the development of human potential is currently the development of an information society, modernization of the economy, social teachings, the vitality of social communities, their self-development, maintenance of social order, the development of economic, political and social spheres, the role of the subjective, human factor in solving the existing problem such issues are covered.